PENGARUH BAP TERHADAP MULTIPLIKASI TUNAS ANGGREK HITAM ( Coelogyne pandurata Lindl ) SECARA KULTUR JARINGAN - Nur'anisa, .; Wulandari, Reine Suci; Asnawati, . (JURNAL HUTAN LESTARI, 2016)
Black Orchid is an orchid endemic in West Kalimantan is currently declining presence, so the ex-situ conservation effort are needed. On of the efforts is to plant propagation by tissue culture methods. This research aimed to get the optimal concentration of Benzil Amino Purine (BAP) for the formation of a black orchid shoot multiplication by tissue culture methods. The research was conducted at the Biotechnology Laboratory of the Faculty of Agriculture, University of Tanjungpura.Â  This study used a completely randomized design (CRD). BAP treatment consists of 6 levels of concentration namely 0 ppm, 0,25 ppm, 0,5 ppm, 1 ppm, 1,25 ppm and 1,5 ppm. The observed variables included the time appeared shoots, number of shoots, and the number of leaves. The results showed that the concentrations of BAP on MS medium significantly affected the entire observation variables. The best concentration for a time appeared shoots and number of shoots was 1,5 and 1,25 ppm BAP, while the best concentration of BAP for number of leaves is 1,5 ppm. Keywords: BAP,Coelogyne pandurata, and Tissue culture